Chat with our AI personalities
i don't get that if it is 2xy +8 or 8 + 2xy then you can't solve or simplify it any further if it were 8 x 2y then you time the 8 by the 2 to get 16y
Y=15/(2c+2x)
x2 + y2 = x2 - 2xy + y2 + 2xy = (x - y)2 + 2xy = 72 + 2*8 = 49 + 16 = 65 You could, instead, solve the two equations for x and y and substitute, but the above method is simpler.
√18xy = √(9*2xy) = √9*√2xy = 3*√(2xy)
2xy + 6 = 4xyz Divide through by 2: xy + 3 = 2xyz 3 = 2xyz - xy = y*(2xz - x) Therefore, y = 3/(2xz - x) provided that 2xz - x is not zero.